Integrated Management Systems (IMS) - García Pantigozo, Manuel (1999)
The culture of standardization is necessary to compete globally, and to this ISO has developed a number of management systems geared to quality, environment, occupational safety and human resources, this means the need to integrate systems through the System integrated Management - GIS